PERBANDINGAN KANDUNGAN FENOLIK TOTAL, FLAVONOIDTOTAL DAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLDAUN JAMBU BOL (Syzigium malaccense L.) DAN DAUN JAMBU AIR KANCING (Syzigium aqueum) - Zahrani Primadiastri, Ilavi; Dwi Wulansari, Endang; Suharsanti, Ririn (Media Farmasi Indonesia, 2021)
Leaves of malay apple (Syzygium malaccense L.) and water apple (Syzygium aqueum) are plants that contain phenolic and flavonoid compounds which have antioxidant activity. The aim of this study was to determine the differences in total phenolic content, total flavonoids and antioxidant activity of ethanol extract of malay apple leaves and water apple leaves. The extraction method uses maceration with 96% ethanol solvent in a ratio of 1:15. The ethanol extract of malay apple leaves and water apple was tested for total phenolic content using the Folin-Ciocalteu method, total flavonoids using the colorimetric method and antioxidant activity using the DPPH method. Qualitative identification of quercetin compounds was performed by densitometry tlc. In the phenolic and flavonoid content test, the total sample extract was made with a concentration of 5000 ppm. In the antioxidant activity test of the extract samples, a series of concentrations of 80, 100, 120, 140 and 160 ppm were made. The results showed that the total phenolic content in the ethanol extract of malay apple leaves has an average of 12.5149 mgGAE/g and water apple leaves of 14.3207 mgGAE/g. The total flavonoid content in the ethanol extract of malay apple leaves has an average of 9.1613 mgQE/g and water apple leaves of 16.5893 mgQE/g. The ethanol extract of malay apple leaves has antioxidant activity with an average IC50 of 138.3315 ppm and water apple leaves of 117.6745 ppm. In qualitative identification densitometry the Rf value of quercetin is 0,68; ethanol extract of malay apple leaves is 0,68 and water apple leaves is 0,85. The results of the independent statistical T test showed that there were differences in the total phenolic content, total flavonoids and antioxidant activity in the ethanol extract of malay apple leaves and water apple leaves.